Karakterisasi Divais Multimode Interference (MMI) Berbahan Polimer untuk Pembagi Daya 1 × 3: Yasin Agung Sahodo, Wina Indra Lavina, Yuni Nur Hidayati, Mefina Yulias Rofianingrum, Banatul Muflihati, Yono Hadi Pramono, Gatut Yudoyono - Yasin Agung Sahodo, Yasin Agung Sahodo; Wina Indra Lavina, Wina Indra Lavina; Yuni Nur Hidayati, Yuni Nur Hidayati; Mefina Yulias Rofianingrum, Mefina Yulias Rofianingrum; Banatul Muflihati, Banatul Muflihati; Yono Hadi Pramono, Yono Hadi Pramono; Gatut Yudoyono, Gatut Yudoyono (Jurnal Fisika dan Aplikasinya, 2025)
A 1 x 3 power splitter devices have been fabricated by using polymer materials and this are characterized by the simulation methods Finite Difference Beam Propagation Method (FD-BPM). Simulations carried ou by applying the phenomena Multimode inteference (MMI). Channel waveguides were fabricated by polyme material, substrate chosen to be acrylic (n = 1.49), core material is Methyl methacrylate (MMA) (n = 1.4905) and cladding layer is acrylic (n = 1,00). Propagation constant used in the simulation is 1.4903412 with 0.6328 um wavelength. Waveguide channel width and length are 50µm and 5000 um. The simulation results show tha the ratio of power output to the input on each channel output by 11%, 37%, and 11% respectively, while the measurement result of the fabrication of 13%, 16%, and 12%. Result of the simulation and fabrication show that this device can be applied in optical communications for power splitter or devider.